2006
DOI: 10.1002/jbm.a.30638
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible laminin‐functionalized hydrogel for neural tissue engineering

Abstract: Traumatic injury to the central nervous system (CNS) triggers cell death and deafferentation, which may activate a cascade of cellular and network disturbances. These events often result in the formation of irregularly shaped lesions comprised of necrotic tissue and/or a fluid-filled cavity. Tissue engineering represents a promising treatment strategy for the injured neural tissue. To facilitate minimally invasive delivery of a tissue engineered system, a thermoreversible polymer is an attractive scaffold cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(145 citation statements)
references
References 39 publications
1
143
0
1
Order By: Relevance
“…A thermoresponsive methylcellulose based hydrogel was prepared by Stabenfeldt et al [93]. Methylcellulose was conjugated to Laminin protein to produce a physically gelling hydrogel capable of producing a suitable environment for neural tissue growth when injected into a defect in the central nervous system [93].…”
Section: Collapsed Network Swollen Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A thermoresponsive methylcellulose based hydrogel was prepared by Stabenfeldt et al [93]. Methylcellulose was conjugated to Laminin protein to produce a physically gelling hydrogel capable of producing a suitable environment for neural tissue growth when injected into a defect in the central nervous system [93].…”
Section: Collapsed Network Swollen Networkmentioning
confidence: 99%
“…Methylcellulose was conjugated to Laminin protein to produce a physically gelling hydrogel capable of producing a suitable environment for neural tissue growth when injected into a defect in the central nervous system [93]. They demonstrated that the addition of the protein conjugate greatly improved the cell viability and adhesion [93].…”
Section: Collapsed Network Swollen Networkmentioning
confidence: 99%
“…Another interesting approach towards a thermosensitive hydrogel system based on methylcellulose was recently reported by Stabenfeldt et al [22]. As it had been shown before [23] that methylcellulose showed low protein adsorption and cell adhesion, Stabenfeldt et al functionalized methylcellulose with the protein laminin, aiming towards the creation of a bioactive scaffold for neural tissue engineering.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…A study in vivo showed that MC exhibited minimal inflammatory tissue reaction following implantation into a TBI lesion cavity (Tate et al 2001). MC was further conjugated with laminin-1 (LN) to promote neuronal cell adhesion and survival (Stabenfeldt et al 2006).…”
Section: Hydrogel In Brain Repairmentioning
confidence: 99%